Sukses Mengembangkan Desain Seni dan Kerajinan Menjahit Aplikasi Berbahan Dasar Limbah Kain (Kain Perca) bagi Industri Rumah Tangga - Titi Indahyani (Bina Nusantara University, 2010)
Arts and craft products are now beginning to be produced by many home industries such as sewing patchwork application products. But the lack of knowledge of art, design and product marketing in this industry making products become less competitive and provide income earning less than the maximum. Besides, home industry players sometimes do not have the high endurance and sustainability in business. As one of the national strategic issues, the arts, crafts and creative industries get serious attention from the government. It is expected with the opening horizons of knowledge in art, design and product marketing in the area of sew patchwork application craft (which is use the waste fabric) will impact the development of entrepreneurship opportunities and support many home industries entrepreneur from local micro become sustainable macro business. This action will also support to further explore the various culture of Indonesian arts, crafts and other creative industries became more creative, innovative and competitive by using waste materials that are environmentally friendly.